First, we'll have to move all terms to one side:

5x^2 - 45 = 0

We'll factorize by 5 to the left:

5(x^2 - 9) = 0

We'll divide by 5 both sides:

x^2 - 9 = 0

We'll re-write the difference of the squares as a product:

(x-3)(x+3) = 0

We'll cancel each factor:

x + 3 = 0

x = -3

x - 3 = 0

x =3

**The solutions of the equation are {-3 ; 3}.**

The equation 5x^2=45 has to be solved.

5x^2=45

Divide both sides of the equation by 5 to cancel the common factor

(5x^2)/5 = 45/5

x^2 = 9

Subtract 9 from both the sides

x^2 - 9 = 0

x^2 - 3^2 = 0

Use the expansion x^2 - y^2 = (x - y)(x + y)

This gives:

(x - 3)(x + 3) = 0

x - 3 = 0 gives x = 3

x + 3 = 0 gives x = -3

The solution of the equation is x = 3 and x = -3

5X^2 - 45 = 0

5( x^2 - 9) = 0

therefore:- (x^2 - 9 ) =0

x^2 = 9

x=squareroot of 3

x = 3